Religious Moderation in the Heart of Tradition: Analysis of Kiai's Preaching Discourse and Yellow Books in Building a Peaceful Narrative in Islamic Boarding Schools - Fadila, Indah Nur; Yenuri, Ali Ahmad (JUPE : Jurnal Pendidikan Mandala, 2025)
This research abstract aims to analyze the role of Kiai's da'wah discourse and the teachings contained within the Kitab Kuning in constructing narratives of peace and religious moderation in Indonesian pesantren. This research is significant due to the strategic position of pesantren as the oldest Islamic educational institutions in Indonesia and the urgent need to instill values of religious moderation in response to increasing intolerance and radicalism in society. The object of this study is the da'wah discourse delivered by Kiai, as well as relevant excerpts from the Kitab Kuning used in the educational process within pesantren. Employing a qualitative approach with discourse analysis methods, this research includes thematic analysis to identify patterns of meaning and in-depth discourse analysis to understand the construction of these narratives. The findings indicate that Kiai's da'wah consistently emphasizes themes of tolerance, mutual respect, and the active construction of peace, strongly supported by principles derived from the Kitab Kuning. Kiai play a central role in interpreting and contextualizing these classical teachings to make them relevant to the lives of santri and contemporary challenges, thereby effectively fostering narratives of peace and moderation within the pesantren environment and broader society. This research concludes that the interaction between Kiai's da'wah and the Kitab Kuning plays a fundamental role in promoting religious moderation and building narratives of peace in pesantren.